Omnipod® Insulin Management System - "patch-pump", as a breakthrough in the treatment of type 1 diabetes - Filipczak, Joanna; Żelazny, Przemysław; Sygacz, Oliwer; Bróż, Sebastian; Dankiewicz, Sara; Swora, Aleksandra; Borowik, Joanna; Brodowski, Wojciech; Pawłowski, Piotr; Basta-Arciszewska, Katarzyna; et al. (Journal of Education, Health and Sport, 2022)
Introduction: There are 425 million adults with diabetes worldwide, 10% of whom have type 1 diabetes. The treatment of choice in this group of patients is insulin delivery. In order to avoid disease-related metabolic disorders, insulin therapy should be planned so that their risk is minimized. This often involves multiple subcutaneous deliveries throughout the day. In order to improve patient satisfaction and comfort, , "smart pumps" have been developed. OmniPod® is the first commercially available pump of this type. Aim of the study: The purpose of our work was to present an innovative form of treatment for type 1 diabetes, to demonstrate the advantages, disadvantages and results of treatment using it. Methods and materials: A literature review was conducted in the PubMed database, using the key words: "diabetes type 1"; "diabetes mellitus"; "OmniPod®"; "insulin"; Results: OmniPod® improves glycemic control and glycated hemoglobin (HbA1c) values over traditional therapies. The algorithm used in the pump ensures normal glycemic ranges throughout the day, without the risk of prolonged episodes of hypo- and hyperglycemia. It improves the quality of life (QOL) index thanks to, among other things, water resistance, lack of difficulties during sleep in contrast to conventional insulin pumps. Conclusion: OmniPod® significantly improves users’ glycemic and HbA1c control. It allows users to forgo conventional insulin pumps or intensive insulin therapy by raising QOL and increasing patients’ sense of proper disease control. Further research should be inclined to evaluate the utility of OmniPod® in other types of diabetes, as well as on the application of the technology in other disease entities.